Primary intra-abdominal hydatid cyst cases with extra-hepatic localization. Issue 2 (2013) - Gündeş, Ebubekir; Küçükkartallar, Tevfik; Çakır, Murat; Aksoy, Faruk; Bal, Ali; Kartal, Adil
No abstract available